PENGARUH BOARD DIVERSITY TERHADAP INTERNET FINANCIAL REPORTING (IFR) - M. Riduan Abdillah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,This research aimed to analyze the influence of board diversity is proxied by the board of commissioners and board of directors gendered female against Internet Financial Reporting (IFR).The population in this research are all manufacturing companies listed in Indonesia Stock Exchange in 2013. Based on purposive sampling method, the number of samples in this research as many as 102 manufacturing companies. Research hypothesis testing using multiple regression analysis with SMART PLS 2.0 M3.The results of hypothesis testing found that the commissioners gendered female and the significant negative effect on the Internet Financial Reporting (IFR). The board of directors gendered female no significant effect on Internet Financial Reporting (IFR).